Pendampingan Periklanan dan Pemasaran Digital Syariah Kepada UMKM Tempe Di Desa Cibatu Purwakarta - Jalaludin, Jalaludin; Kurniaputri, Mega Rachma; Herdi, Rahmawati; Imam, Saepul (STIE Syariah Indonesia Purwakarta, 2025)
Based on the observation results, the PKM team found several unique phenomena related to Tempe MSMEs in Cibatu Village, one of which is the largest number of Tempe MSME players in Cibatu Village when compared to other MSME players. The second phenomenon is that the digital marketing used is still very simple, namely using Whatsapp media, not using other social media that are popular today. The third phenomenon, at the business location of Tempe MSME players there are no instructions for tempeh production, and the business location has not been registered on google maps, so many people do not know that the location produces tempeh. The purpose of this PKM is to provide sharia-based digital advertising and marketing assistance to Tempe MSME players in Cibatu Village. The method used in this PKM is to go to the field to make observations, provide solutions to problems, implement the solutions offered, supervise and evaluate Tempe MSMEs in Cibatu Village. Based on the discussion above, it can be concluded that community service on advertising media assistance and sharia digital marketing, Tempe MSME players have understood 87.5% of the importance of banner advertising media to promote their products, 90% of Tempe MSMEs already understand and use whatshapp and Instagram promotional digital media, and the location of Tempe MSMEs has been registered on google maps. The hope is that consumers of Tempe UMKM Cibatu will increase, and profits will also increase, so that Tempe UMKM in Cibatu can help the Cibatu Village community even more through the creation of jobs.